2015
DOI: 10.1080/09168451.2014.991685
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antimicrobial efficacy of natural plant-derived compounds against Vibrio cholerae of O1 El Tor Inaba serotype

Abstract: Shin (2015) Invitro and invivo antimicrobial efficacy of natural plant-derived compounds against Vibriocholerae of O1 El Tor Inaba serotype, Bioscience, Biotechnology, and Biochemistry, 79:3, 475-483, DOI: 10.1080/09168451.2014 In this study, we investigated antibacterial activities of 20 plant-derived natural compounds against Gram-negative enteric pathogens. We found that both flavonoids and non-flavonoids, including honokiol and magnolol, possess specific antibacterial activities against V. cholerae, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Honokiol and 4′-O-methylhonokiol consist of a 5,3′-diallylbiphenyl skeleton bearing hydroxy group in the C2 of the A ring, or hydroxyl and methoxy groups in the C4′ of the B ring, respectively. The previous study 11) showed that 4′-O-methylhonokiol exerts higher anti-inflammatory activity than those of honokiol and various honokiol analogs, as examined using COX-1 and COX-2 enzyme assay and LTB4 formation assay. Thus, we contemplated efficient synthesis of mono-alkylated analogs on either the 2-or 4′-position for elongating the regioselective chain and designing site-selective photoaffinity probes, which would be useful to elucidate directly binding proteins, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Honokiol and 4′-O-methylhonokiol consist of a 5,3′-diallylbiphenyl skeleton bearing hydroxy group in the C2 of the A ring, or hydroxyl and methoxy groups in the C4′ of the B ring, respectively. The previous study 11) showed that 4′-O-methylhonokiol exerts higher anti-inflammatory activity than those of honokiol and various honokiol analogs, as examined using COX-1 and COX-2 enzyme assay and LTB4 formation assay. Thus, we contemplated efficient synthesis of mono-alkylated analogs on either the 2-or 4′-position for elongating the regioselective chain and designing site-selective photoaffinity probes, which would be useful to elucidate directly binding proteins, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we found that modifications of 4′-Omethylhonokiol through introduction of methyl, isopropyl, and prenyl groups at phenol slightly decrease the inhibitory activity of COX-2 enzyme. 11) Compared with other synthesized analogs, 11a showed the most promising anti-inflammatory activity; thus, it was exploited as an intermediate to obtain C4′-labeled photoaffinity probe of honokiol. 25) By the treatment with trifluoroacetic acid in dichloromethane, the tertbutyl ester group of 11a was removed to afford carboxylic acid 12, as shown in Chart 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wogonin was isolated from the roots of S. baicalensis using a previously described method (Kim et al, 2001) and honokiol and magnolol were also reported previously (Kim et al, 2015).…”
Section: Natural Plant-derived Compoundsmentioning
confidence: 99%